Differential correlation of white matter hyperintensity with Alzheimer's pathology within A/T groups. (31st December 2021) - Alban, Sierra; Choupan, Jeiran; Ringman, John M.; Toga, Arthur W.; Chui, Helena C.; Sepehrband, Farshid
Abstract: Background: White Matter Hyperintensities (WMH) of brain MRI have been linked to cerebral amyloid angiopathy, a hallmark of Alzheimer's Disease (AD). Particular biomarkers, such as Florbetapir and Flotaucipir PET measures of β‐amyloid and neurofibrillary tangles, respectively, have been utilized to quantify AD pathology (A/T). Here we investigated WMH association with AD pathology across A/T groups. Method: Imaging was gathered from ADNI (N=286, 137 male). Participants were stratified based on A/T. For Aβ classification, amyloid PET SUVR data was analyzed. Flortaucipir SUVR PET in metatemporal regions was used (Jack et al. 2017). The cutoffs used to categorize A+ and T+ were any values above 1.25 and 0.79 respectively. A deep convolutional neural network was used for mapping WMH in MRI (Sepehrband et al., 2020). Regression and Pearson correlation analysis were used to assess the association and correlation between WMH and amyloidosis (controlling for age, sex, education and scanner manufacturer). Result: WMH volume was positively correlated with amyloidosis (Figure 1A; r =0.28, p =6e‐7). We observed a significant effect of the WMH volume on global amyloid SUVR ( F (1, 309) = 7.95, p = 0.008). WMH volume of participants with Amyloid (A+) or Tau (T+) pathology was higher than controls (A‐/T‐) (Figure 1B). WMH volume of AD participants(A+/T+) was significantly higher than controls (A‐/T‐) ( p = 0.007, Cohen's d = 0.4). A+/T‐ participants had higher WMH than control ( p = 0.002, Cohen's d = 0.5). We observed significant positive correlation between WMH and amyloid in the A+/T‐ group ( r =0.36, p =0.0008) (Figure 1C). A marginal positive correlation was observed among A‐/T+ participants ( r =0.58, p =0.0498), and a positive non‐significant correlation among the A+/T+ group ( r =0.23, p =0.09). We observed neither a correlation nor an association between WMH and Tau uptake (Figure 1D: correlation p =0.25; association p =0.4). Conclusion: Increased global flortaucipir uptake was associated with an increase in overall WMH volume. The strongest relationship between WMH and amyloid accumulation was when neurodegeneration was not present (A+/T‐). These findings are consistent with autopsy studies showing correlations between cerebral amyloid angiopathy and WMH. The combination of significant WMH and a positive amyloid PET scan raises possibility of underlying amyloid angiopathy.